Pelatihan Komputer untuk Meningkatkan Keterampilan Bidang Administrasi Pengurus Unit Kerja Karang Taruna (UKKT) RW 06 Mampang, Jakarta Selatan - Sartini, Sartini; Saryoko, Andi; Sari, Retno; Siti Nurhasanah Nugraha; Dicky Kurniawan, Muhammad (LPkM Universitas Bakrie, 2022)
At this time digital technology makes it easier for everyone to disseminate and get information quickly, and makes it easier for us to get the information we want. Digital technology has been used in all areas of life, one of which is education. Increasing the mastery of digital science and technology is not only carried out in formal education, but also in non-formal education. Skills in using computers which are basic skills to be able to apply digital technology are very necessary, including in the field of storage and administrative data processing. The problem faced by the management of UKKT RW 06 is the lack of skills in using computers for administrative management activities. Increased skills in the use of computer-based software technology applications greatly assist the management of UKKT RW 06 in administrative management activities so that they become more effective and efficient. This has prompted the holding of administrative skills training activities for UKKT RW 06. The purpose of this computer training is to improve the administrative skills of UKKT RW 06 administrators so that they can assist in the process of correspondence and processing of incoming and outgoing funds to be more effective and efficient. The evaluation results from the preparation, implementation, monitoring and evaluation stages based on the answers of 19 participants, it can be concluded that for each question given, on average, participants choose the agree and strongly agree scales. This means that participants are satisfied with the community service activities in the form of computer training so that they can help improve the skills of participants in using Microsoft Office for administrative management activities.